Strategic objectives of corporate venture capital as a tool for open innovation - Felix Pinkow; Jasper Iversen (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Corporations are confronted with challenges adjusting to changing technologies and markets. Seeking innovations externally through open innovation is a possible approach to go beyond the internal development of innovations. One practice of open innovation to assimilate external knowledge is corporate venture capital (CVC), meaning minority investments in entrepreneurial ventures by incumbent firms, whereby the objectives of CVC investments might be purely financial or may pursue strategic goals. CVC has been identified as a possible approach to ambidexterity, since investments in new ventures can allow to explore new technologies and markets, or to improve internal exploitative capabilities. Although literature on the potential strategic benefits of CVC is abundantly available, a systematic conceptualization of strategic objectives is lacking. Therefore, this paper examines strategic objectives of CVC and seeks to enrich, extend and conceptualize existing research through a theoretical framework. The conceptual foundation of this study embeds CVC in the ambidexterity literature, and clusters objectives of CVC investments in view of an ambidextrous organization and the degree of autonomy given to CVC units. The strategic objectives that can be pursued through CVC investments are (a) strengthening the core business, (b) leveraging the ecosystem, and (c) exploring new markets and technologies. This study concludes with a comprehensive overview of the strategic objectives that can be pursued by CVC, illustrates the barriers and limitations of CVC investments, and discusses the role of autonomy and ambidexterity with respect to the individual strategic objectives. Hereby, CVC is identified as a powerful approach to engage in open innovation practices, since it allows one to pursue a range of different strategic objectives through tapping into external knowledge held by new ventures. Often considered an approach for exploring new technologies through external knowledge acquisition, CVC is also identified as an open innovation approach that allows organizations to increase their internal exploitation capabilities.
Keywords: 650; open innovation; ambidexterity; innovation management; corporate venture capital; CVC; exploration and exploitation; framework development; literature review; new technologies; technology entrepreneurship